PERAN KOMUNIKASI PENDIDIKAN DALAM PROSES BELAJAR MENGAJAR DI SEKOLAH - Adellia Pirtika Putri Lubis; Siti Hadjerah; Sintya; Safvhira Rahma Rosalia; Safina Dewi; Nazwa Afrilia; Nadya; Jesica Bilkisti; Firly Rahmadani; Elma Kencana; Bunga Dwi Azzahra; Anin Ramaida; Ere Mardella Arbiani (Jurnal Riset Multidisiplin Edukasi, 2026)
As social beings, humans live in groups and need one another; interaction and communication are integral parts of daily life. Communication plays a crucial role in human life, in line with its persuasive, educational, and informative functions. The objective is to create a pleasant, comfortable, and stress-free learning environment. This scientific article employs a systematic literature review method to examine and synthesize relevant conceptual theories, based on literature analysis from various scholarly sources. References were collected through searches in academic databases such as Google Scholar, as well as from books and indexed national journals. Communication also serves as a means for control, motivation, emotion management, information dissemination, discussion, socialization, entertainment, education, and cultural development. Thus, effective communication between educators and learners in the learning process is expected to be realized. Educational communication has several roles: creating a conducive learning climate, facilitating the delivery of lesson materials, increasing learning motivation and interest, developing social and emotional skills, and evaluating the learning process and outcomes.